THE ESSENTIAL OILS OF FOUR ENDEMIC SALVIA SPECIES IN TURKEY: S. DIVARICATA, S. ERIOPHORA, S. LONGIPEDICELLATA AND S. PILIFERA - Kurkcuoglu, M.; Duran, A.; Baser, K. Hüsnü C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Salvia (Labiatae) is represented in Turkey by 94 taxa belonging to 89 species with 50 % endemism (1, 2). Water distilled essential oils from the aerial parts of four endemic species of Salvia from Turkey were analysed by GC and GC/MS. oil yield (%) and main components (%) were as follows: Salvia divaricata 0.87 1,8-cineole (34.4), linalyl acetate (10.3), Salvia eriophora 0.80 caryophyllene oxide (13.7), heptacosane (8.9), Salvia longipedicellata trace alpha-caryophyllene (47.9), alpha-humulene (11.5), Salvia pilifera 0.18 alpha-pinene (9.4), myrcene (5.3), ar-curcumene (5.1) References: 1. Hedge, I.C., 1982, Salvia, Flora of Turkey and East Aegean Islands; Univ. Press: Edinburgh, P.H. Davis (Ed.), Vol.7, 400-461. 2. Ba?er, K.H.C. 2002. Aromatic Biodiversity Among the Flowering plant taxa of Turkey, Pure Appl.Chem., 74 (4):527-545.